English For Fun: Meningkatkan Kecakapan Bahasa Inggris Siswa Sekolah Dasar melalui Pembelajaran Interaktif di SD Negeri 4 Halong - Marasabessy, Halima; Que, Stella Rose (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2024)
The English for Fun Community Service Program was conducted to enhance the English language skills of students at SD Negeri 4 Halong through an interactive and enjoyable learning approach. The program ran for five days, from Monday to Friday, covering topics such as weather, profession, numbers, and animals. Each session was designed using the learning by playing concept, which combined visual, auditory, and kinesthetic activities such as singing, using picture cards, and participating in group games. The implementation consisted of three main stages: preparation, execution, and evaluation. The results showed an improvement in students’ basic vocabulary mastery as well as increased enthusiasm toward learning English. In addition to benefiting the students, the program also provided valuable learning opportunities for university students to gain real teaching experience and foster social empathy. Collaboration among students, teachers, and the school played a key role in the success of the program. Moving forward, similar activities are expected to be further developed with more diverse materials and broader community involvement.